Mycobacterium tuberculosis - the 10 years of epidemiological and diagnostics studies - Boruń-Popławska, Marta; Sajduda, Anna; Brzostek, Anna; Dziadek, Jarosław (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2005)
Tuberculosis (ТВ) is the main bacterial pathogen that causes more deaths than AIDS, malaria and all infectious diseases. The unusual long doubling time (about 24h), highly hydrophobic cell envelope resistant to chemical lysis was the reason to delay the molecular study of this bacteria. Fifteen years ago, we did not have any molecular tools and methods for genetic manipulation or isolation and analysis of intracellular protein and nucleic acids. Today we have many useful shuttle or integration vectors for basic study of mycobacteria. The full sequence of M. tuberculosis genome is already known. At the present time the diagnosis of tuberculosis is supported with fast-culture system BACTEC and molecular techniques based on PCR and DNA hybridization. The mechanisms of resistance to antituberculosis drugs were described, and first identification of resistance profile is available by using PCR and sequencing or real time PCR methods. In our group in the Center for Microbiology and Virology Polish Academy of Sciences and in the Dept, of Genetics of Microorganisms, University Łódź we have characterized new insertion sequences from M. tuberculosis complex- 18990 and IS1607. In diagnostic studies we have proposed the DIG-PCR ELISA assay as a reliable, specific and sensitive test to identify M. tuberculosis directly in clinical samples. We have performed wide epidemiological studies of M. tuberculosis strains isolated from Polish ТВ patients including drug - and multidrug - resistant strains. Finally we identified the most frequently present mutations responsible for drug resistance of polish clinical isolates of M. tuberculosis.